El yo kantiano como sujeto de atribución o espacio lógico: La traducción de un fragmento del §17 de la Crítica de la razón pura - Stepanenko, Pedro (Con-Textos Kantianos. International Journal of Philosophy, 2024)
In §17 of the Critique of Pure Reason, Kant formulates the principle of the synthetic unity of apperception, the foundation of all cognition, using the German verb "rechnen" to specify the relation of sensible representations to the self (B 138). In this paper, I show how different ways of translating this verb support conflicting understandings of the identical self, corresponding to that unity. On the one hand, there is the understanding of the self as a subject that is determined through the attribution of its representations, on the other, the conception of the self as a logical space in which representations are specified by their reference to objects.